Implementation of a Social Emotional Learning-Based Psychoeducation Program to Improve Friendship Quality Among Adolescents - Blesya Flaratu Risa; Ellen Chai; Jesica Elisabet BR Tarigan; Pamela Hendra Heng; Hanna Christina Uranus (PT Keberlanjutan Strategis Indonesia, 2025)
High-quality friendships are an important factor in adolescents' social and emotional development. However, observations and interviews at KK Orphanage revealed several social relationship problems, including unresolved conflicts, communication misunderstandings, social rejection, and low openness in interaction. These conditions were reinforced by the pre-test results using the Friendship Qualities Scale (FQS), which showed an average friendship quality score of 35.35%. This program aimed to examine the effectiveness of a Social Emotional Learning (SEL)-based psychoeducation program in improving friendship quality among adolescents. The program used a quantitative approach with a one-group pretest-posttest design involving eight adolescents aged 14-17 years living at KK Orphanage. Data were collected using the FQS before and after the intervention. The intervention consisted of 12 sessions focusing on self-awareness, emotional regulation, empathy, interpersonal communication, cooperation, conflict resolution, and trust building. The results showed an increase in the average friendship quality score from 35.35% at pre-test to 73.87% at post-test, with an improvement of 38.52%. These findings indicate that the SEL-based psychoeducation program was effective in improving the quality of adolescent friendships in an orphanage setting.